Detection of illegal use of mobile communication operators resources - Теленик, С. Ф.; Ролик, А. И.; Малюков, П. Н.; Пищаева, Н. Н. (Problems of Informatization and Control, 2009)
Approach is presented for the rapid and effective analysis of temporal rows, displaying concrete processes in-process provider of mobile communication. The offered solution is based on the method of segmentation of curves and use of sliding window for organization of monitoring of row, and for the analysis of traffic modification of algorithm of voting of estimations is offered with the use of similarity measure